Hypotheses of development and strategies for overcoming drug resistance in epilepsy. Рart II: Overcoming strategies - A. M. Yakimov; E. E. Timechko; A. I. Paramonova; A. A. Vasilieva; F. K. Rybachenko; A. D. Rybachenko; D. V. Dmitrenko (Эпилепсия и пароксизмальные состояния)
To date, despite the complexity and risks of not removing seizures hippocampal resection is the only effective solution to overcome drug resistance in epilepsy. Recently, a significant amount of data has been accumulated on the mechanisms of drug resistance development, which allows to develop innovative strategies to overcome it. New antiepileptic drugs have been emerging, directly aimed at acting on disease etiological substrate (many of them are at the stage of clinical trials). Targeted therapy have been extensively introduced, and coupled with precision medicine methods can potentially aid in finding a personalized approach to each individual patient. Migraine models also achieve a qualitatively new level, providing researchers an opportunity to develop highly effective systems for identifying previously unknown disease components, as well as assessing an effect of new drugs. The aim of this review was to highlight current approaches to the treatment of epilepsy and overcoming drug resistance.